Indications and route of hysterectomy for benign diseases: guideline of the DGGG, OEGGG and SGGG (S3 Level, AWMF Registry No. 015/070, April 2015) = Indikation und Methodik der Hysterektomie bei benignen Erkrankungen - Neis, Klaus Joachim; Kleine, Werner; Schmidt, Dietmar (Geburtshilfe und Frauenheilkunde, 2016)
Background: Official guideline “indications and methods of hysterectomy” to assign indications for the different methods published and coordinated by the German Society of Gynecology and Obstetrics (DGGG), the Austrian Society of Gynecology and Obstetrics (OEGGG) and the Swiss Society of Gynecology and Obstetrics (SGGG). Besides vaginal and abdominal hysterectomy, three additional techniques have been implemented due to the introduction of laparoscopy. Organ-sparing alternatives were also integrated. Methods: The guideline group consisted of 26 experts from Germany, Austria and Switzerland. Recommendations were developed using a structured consensus process and independent moderation. A systematic literature search and quality appraisal of benefits and harms of the therapeutic alternatives for symptomatic fibroids, dysfunctional bleeding and adenomyosis was done through MEDLINE up to 6/2014 focusing on systematic reviews and meta-analysis. Results: All types of hysterectomy led in studies to high rates of patient satisfaction. If possible, vaginal instead of abdominal hysterectomy should preferably be done. If a vaginal hysterectomy is not feasible, the possibility of a laparoscopic hysterectomy should be considered. An abdominal hysterectomy should only be done with a special indication. Organ-sparing interventions also led to high patient satisfaction rates, but contain the risk of symptom recurrence. Conclusion: As an aim, patients should be enabled to choose that therapeutic intervention for their benign disease of the uterus that convenes best to them and their personal life situation.